Appreciating Factors Beyond the Physical in Talent Identification and Development: Insights From the FC Barcelona Sporting Model - Doncaster, Greg; Medina, Daniel; Drobnic, Franchek; Gómez-Díaz, Antonio José; Unnithan, Viswanath (Frontiers in Sports and Active Living, 2020)
FC Barcelona is a multi-sport organization that adopts a talent identification approach that emphasizes the technical, psychological, and perceptual–cognitive attributes. It is unclear within this type of sporting selection model whether the relative age effect (RAE) exists. Consequently, the aim of the study was to evaluate the RAE across multiple sports and age groups at FC Barcelona. The birthdates of all players (n = 6,542) affiliated to each sport [male basketball (n = 1,013), male (n = 3,012) and female (n = 449) soccer, male futsal (n = 761), male handball (n = 999), and male indoor roller hockey (n = 308)] across all age groups from U10 to Senior were recorded. These were then categorized into quartiles from the start of the selection year (Q1 = Jan–Mar; Q2 = Apr–Jun; Q3 = Jul–Sep; Q4 = Oct–Dec) and analyzed for (a) each sport; (b) each age group, irrespective of the sport; and (c) each age group within each sport, using Chi-squared statistics and odds ratios (ORs) with 95% confidence intervals (CIs). Birthdates across the entire club revealed a RAE (Q1 = 46.1%, Q2 = 27.1%, Q3 = 17.1%, and Q4 = 9.7%, χ2 = 29.8, P < 0.01), with OR in Q1, Q2, and Q3 representing a 4.76 (95% CIs: 1.96–11.57), 2.80 (1.12–7.03), and 1.77 (0.67–4.63) increased likelihood for selection when compared to Q4, respectively. Despite FC Barcelona's approach to talent identification and development, the RAE was still present within youth age groups (<18 years old). The current findings provide support that the RAE is more prevalent within regionally popular sports and reduces with increasing age; however, given the talent identification processes within FC Barcelona's sporting model, additional factors beyond the physical attributes, such as enhanced psychological and perceptual–cognitive attributes, in those born earlier in the selection year might further influence the RAE. Consequently, current results provide indirect evidence to suggest that sociological and psychological determinants might be a greater influence on the presence of RAE in sporting environments that prefer to consider technical and perceptual–cognitive attributes in their talent development programs.